Crystal structure of trans-diaqua-bis(salicylaldehydato-O,O′) chromium(III) chloride, [Cr(C7H5O2)2(H2O)2]Cl - Zhu H.-L.; Qu Y.; You Z.-L.; Tan M.-Y.; Liu W.-S.; Ma J.-L. (Zeitschrift für Kristallographie - New Crystal Structures, 2003)
C14H14ClCrO6, monoclinic, P121/c1 (No. 14), a = 8.998(18) Å, b = 18.68(4) Å, c = 4.945(10) Å, β = 105.95(2)°, V = 799.2 Å3, Z = 2, Rgt(F) = 0.069, wRref(F2) = 0.170, T = 298 K.